NAVIGATING CHALLENGES IN ARABIC PEDAGOGY: INTERROGATING THE ROLE OF SCIENCE AND TECHNOLOGY - Aminullahi A. R., (JOEL: Journal of Educational and Language Research, 2024)
Arabic plays a crucial role on the global stage, being deemed indispensable. Within the United Nations, three languages are officially recognised: Arabic, French, and English. However, unlike its counterparts, Arabic receives limited support from the Nigerian government. Despite being a subject offered at both Junior and Senior Secondary School levels, the approach to teaching Arabic needs enhancement to captivate and stimulate the learners' interest. This study delves into the traditional methods employed by Arabic teachers in the past, which have inadvertently discouraged students from selecting Arabic for their professional development. The paper explores how incorporating science and technology can serve as a remedy to make Arabic more appealing and interesting to students. Furthermore, the introduction of new ideas, innovations, techniques, and scientific and technological instructional materials is considered to be a potential solution for effective teaching and learning of Arabic literature